What do we mean by 'systematic' in health education systematic reviews and why it matters!. (3rd August 2019) - Gordon, Morris; Daniel, Michelle; Patricio, Madalena
Abstract: For anyone who reads the health education literature regularly, journal sections that focus on "reviews" are common, yet the use of the term "systematic" to describe these reviews is sporadic. Further, we believe this term is used in a manner in the field that does not accurately reflect the methodological implications of the term in this context. There are examples of "systematic" works that simply don't describe themselves in that way, despite a clear alignment with many of the principles of "systematic reviewing". Conversely, there are reviews that are clearly not systematic, yet describe themselves as such. In this piece, we discuss how this difficulty with methodological nomenclature has occurred and the distinct and important meaning of the term "systematic" in relation to health education reviews.